Retrospective evaluation of canine palpebral masses treated with debulking and cryotherapy: 46 cases. (27th July 2018) - Zibura, Ashley E.; Henriksen, Michala de Linde; Rendahl, Aaron; Lim, Christine C.; Reilly, Christopher
Abstract: Purpose: To evaluate the recurrence frequency and the time to recurrence of canine palpebral masses treated with debulking and cryotherapy. Methods: Medical records of dogs that underwent debulking and cryotherapy for palpebral masses from December 2010 to November 2015 at the University of Minnesota's Veterinary Medical Center were reviewed. A telephone survey with owners was used to determine recurrence and time to recurrence. Results: Forty‐six masses (31 dogs) were included in this retrospective study. Included palpebral masses were as follows: adenomas 17/46 (37%), epitheliomas 8/46 (17.4%), papillomas 6/46 (13%), inflammatory masses 6/46 (13%), mixed adenoma‐papillomas 6/46 (13%), mixed epithelioma‐papillomas 2/46 (4.4%), and a melanocytoma 1/46 (2.2%). Of the seven masses that were noted to recur (7/46, 15.2%), three were mixed adenoma‐papillomas (three of six adenoma‐papillomas, 50%), two were epitheliomas (two of eight epitheliomas, 25%), one was a papilloma (one of six papillomas, 16.7%), and one was a melanocytoma (one of one melanocytoma, 100%). Average recurrence time was 367.9 days [range: 30‐904 days]. A significant association between tumor type and tumor recurrence was found ( P  = .009). Adenomas were significantly less likely to recur ( P  = .017), and mixed adenoma‐papillomas were significantly more likely to recur ( P =  .001). Conclusions: Debulking and cryotherapy is an effective method of treatment for eyelid masses in dogs with a low study recurrence rate of 15.2% and average recurrence time of 367.9 days. Results also suggest that mixed adenoma‐papilloma masses have a significantly higher recurrence rate than other eyelid masses, whereas adenomas had no recurrence in our study population.